Cleaning interactions between shrimps (palaemonidae) and freshwater stingrays (potamotrygonidae) in the Paraná River, Southeastern Brazil - Garrone-Neto, Domingos [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Zuanon, Jansen; Carvalho, Lucélia Nobre (My University, 2014)
We report the first record of cleaning symbiosis between a river stingray, Potamotrygon falkneri, and a palaemonid shrimp, Macrobrachium jelskii. Shrimps of different sizes were observed cleaning adult stingrays partially buried in sandy substrate and shallow water, during the day in the Parana River, Southeastern Brazil, in four events. The presence of ectoparasites in the P. falkneri individuals was not detected during the cleaning interactions, and the shrimps were probably consuming dead tissue and/or mucus. Thus, the cleaning activity of the palaemonid shrimps was considered commensal and not casual. Despite P. falkneri including palaemonid shrimps in its diet, the low diurnal activity of this predator and a possible state of gastric repletion by the stingrays may have facilitated the cleaning interaction.